Memaksimalkan kemampuan pemecahan masalah siswa kelas X pada materi vektor dengan menerapkan model discovery learning terintegrasi pembelajaran diferensiasi gaya belajar - Dewi Lukitawanti, Sartika; Istyowati, Anik; Yuli Pratiwi, Hestyningtyas (Universitas Negeri Malang, 2023)
This research was conducted to maximize students problem-solving abilities by applying the Discovery Learning model integrated with learning style differentiation. The sample or research subject consisted of one class, namely class X-2 with a total of 35 students who would be grouped according to their visual, auditory, and kinesthetic learning styles. The instruments used to measure students' problem-solving abilities after being given treatment were five essay questions covering several indicators, namely Useful Description, Physics Approach, Specific Application of Physics, Mathematical Procedures, Logical Progression. The research design used in this study was Classroom Action Research (CAR) with 3 cycles where each cycle consisted of 1 meeting. The results of this study were divided into two, namely the average value of students' problem solving abilities on vector material in the pre-cycle stage of 21.80, the first cycle was 37.20, the second cycle was 66.03, and the third cycle was 82.54 and In terms of the percentage of learning implementation, it was found that the first cycle was 79.68%, the second cycle was 82.10%, and the third cycle was 89.20%. Thus, it can be said that in order to maximize students' problem-solving abilities in vector material, they can apply the Discovery Learning model integrated with learning style differentiation learning.